Impact of Prison Experience on Anti-gay Sentiments: Longitudinal Analysis of Inmates and Their Families - Maxim Ananyev; Mikhail Poyker (Institute of Labor Economics (IZA), 2024)
Inmates' informal code often ascribes low status to persons perceived as passive homosexuals. We use longitudinal data to investigate whether prison experience contributes to anti-gay beliefs. We find that prison experience prompts a higher level of anti-gay sentiments among males and their families, while no discernible difference exists before incarceration. We find no effect for female ex-prisoners. We confirm that the results are not driven by pre-incarceration trends, changes in trust and social capital, socioeconomic status, mental health, masculinity norms, and other potential alternative explanations. Our study sheds light on the overlooked role of prisons as a significant contributor to the propagation of anti-gay attitudes.
Keywords: J15; M14; H76; K42; P00; R29; Z13; 330; tolerance; homosexuals; incarceration; Australia